Feasibility of duckweed as poultry feed-A review - ISLAM, K M S (The Indian Journal of Animal Sciences, 2014)
Duckweed (Lemnaceae), tiny free-floating vascular plants. have 4 common genera, Spirodela, Lemna, Wolffia and Wolffiella, and about 40 species are world wide distributed. It attracted considerable attention for utilization as protein supplement in poultry ration to minimize chronic scarcity!and high cost of animal protein supplements. Crude protein (CP) content of duckweed (DW) is 7 to 40 % on dry matter basis depending on media where it was grown and the species involved. The essential amino acid (EM) profile ofDW is similar to other animal proteins with the exception of methionine. It contains 4g lysine/100g protein and it is comparable to other sources of protein. Their production rate of about 80 metric ton/ha/year of solid material is higher than other classic crops like alfalfa, soybean etc. Dried duckweed (DW) can be used in poultry diet as partial replacement of fish-meal, soybean-meal, alfalfa leaf-meal etc. It may be included as a part of protein concentrate mixture for layer and broile . Its inclusion level is up to 15% in broiler ration and 40% in layer diet. Simultaneously, it may be useful for the treatm nt of waste-water and already being used in many developed countries. After reviewing these aspects it is suggested the DW could be used as an effective protein supplement in poultry diet.